1982
DOI: 10.1002/jez.1402230202
|View full text |Cite
|
Sign up to set email alerts
|

Taurine transport by isolated flounder renal tubules

Abstract: Previous in vivo clearance studies (Schrock et al., '82) have revealed that taurine is secreted by marine fish kidneys. In the present study taurine secretion by the flounder (Pseudopleuronectes americanus) renal tubule was investigated by assaying the transport of 14C-taurine in vitro. Collections from isolated fluid-secreting flounder tubules confirmed the presence of a tubular mechanism for taurine secretion. The flounder renal tubule concentrated taurine in the lumen at a lumen/bath ratio of 25, with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…The substitution of choline for sodium or gluconate-for CPalmost completely inhibited taurine uptake on both surfaces. Also, the taurine transporter at both surfaces was like those described in other tissues (9,10,(13)(14)(15) in that taurine uptake was inhibited by #-amino acids, hypotaurine and #l-alanine, but not by an a-amino acid, L-alanine. We did not determine the apparent affinity of the transporter for other fl-amino acids compared to its affinity for taurine.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…The substitution of choline for sodium or gluconate-for CPalmost completely inhibited taurine uptake on both surfaces. Also, the taurine transporter at both surfaces was like those described in other tissues (9,10,(13)(14)(15) in that taurine uptake was inhibited by #-amino acids, hypotaurine and #l-alanine, but not by an a-amino acid, L-alanine. We did not determine the apparent affinity of the transporter for other fl-amino acids compared to its affinity for taurine.…”
Section: Resultssupporting
confidence: 60%
“…Plasma taurine is -50 MM (8). Taurine is accumulated during hypertonicity or released during shift to lower osmolarity by tissues in fish (14,21,27), by Ehrlich ascites tumor cells (15,17), and in most (23)(24)(25), but not all (26) studies of rat brain. In this study we found that taurine uptake and release by MDCK cells was regulated by medium osmolarity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been assumed that during cerebral cell volume regulation, fluctuations in the cytosolic levels of osmolytes are mediated by release and reuptake of osmolytes into subcellular sequestration sites (2,7). However, recent data in flounder erythrocytes (38), skate renal tubules (23), mammalian brain cells (35,37,39), and renal medullary cells (40)(41)(42) indicate that regulation of transmembrane flux of osmoprotective molecules is a critical component of cell volume regulation during exposure to anisotonic media. Oral administration of taurine analogues to rats before induction of hypernatremic dehydration supplements the cerebral pool of osmolytes and confers protection against cell shrinkage during hypernatremia (8).…”
Section: -H Chd (%)mentioning
confidence: 99%